2009
DOI: 10.1111/j.1471-4159.2009.06106.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C regulation of neuronal zinc signaling mediates survival during preconditioning

Abstract: Abbreviations used: KCN, potassium cyanide; MRE, metal response element; MT, metallothionein; MTF-1, metal response element transcription factor-1; PKC, protein kinase C; shRNA, short hairpin RNA; TPEN, N,N,N¢,N¢-tetrakis (2-pyridalmethyl)ethylenediamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
73
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 51 publications
6
73
0
4
Order By: Relevance
“…Although numerous studies have suggested that various PKC isoforms are involved in neuronal survival and death (Aras et al, 2009;Miller et al, 2009;Nelson and Alkon, 2009), the role of PKCs in oxidative stress induced toxicity to OLs has not been elucidated. In this study, we found that PKCs are important signaling proteins involved in the cell death pathways triggered by the potent oxidant, peroxynitrite.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have suggested that various PKC isoforms are involved in neuronal survival and death (Aras et al, 2009;Miller et al, 2009;Nelson and Alkon, 2009), the role of PKCs in oxidative stress induced toxicity to OLs has not been elucidated. In this study, we found that PKCs are important signaling proteins involved in the cell death pathways triggered by the potent oxidant, peroxynitrite.…”
Section: Discussionmentioning
confidence: 99%
“…In several animal models of cerebral ischemia, Zn 2þ chelation has consistently been shown to reduce neuronal death (16,53). However, emerging in vivo and in vitro studies suggest that a sublethal increase in neuronal free Zn 2þ may also trigger pathways that limit cell injury after injury and confer longterm tolerance (5,65). The mechanisms accounting for the free Zn 2þ accumulation and downstream signaling pathways mediating neuroprotection may provide novel therapeutic targets for regulating intracellular Zn 2þ signals, and ultimately cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that preconditioning stimuli induce the sublethal activation of cell death factors that trigger survival pathways, which, in turn, prevent subsequent lethal injurious signaling (32). Along these lines, a novel role for Zn 2þ as an important, early signal in the initiation of survival pathways critical to neuronal tolerance has emerged (5,65). The results from these studies offer insights into endogenous mechanisms that protect neurons in the face of lethal cellular injury.…”
mentioning
confidence: 90%
See 2 more Smart Citations